DETECTION OF DNA ANALYSIS (DEOKSIRIBO NUCLEIC ACID) COMPUTER SYSTEM WITH HUMAN BIOLOGY - Rendi Adiwijaya; Sahni Damerianta P, SKom, MMSI (Jurnal Sistem Informasi, 1999)
The existence and use of computer systems biology, which can give the appearance of pictorial information, which is more supportive in the determination of the genetic code of the structure of DNA derivatives (Deoksiribo Nucleic Acid). In principl e, this detection system using image processing as the basis of the work process. Because the reading of objects or samples which have been studied, performed with the enlargement and improvement of the resolution of pixels (small dots in the figure).  This system requires some specific hardware, such as electron microscope with a blend of at least 35mm- lens digital camera and a computer with at least a PII processor with 64 Mbytes memory.